Strategy The Development of The Business Sector of The Tourism Industry Through The Role of Staycation The Pandemic Covid-19 (Studies Syariah Hotel Surakarta) - Wibowo Isa; Mei Candra Mahardika (Universitas Muhammadiyah Jakarta, 2022)
Pandemic Covid-19 that hit Indonesia, providing great influence in various sectors. One of them in the tourism sector, which have an impact on the occupancy rate of the hotel. People who do travel has decreased so that the impact on hotel occupancy that come down. This is happening at Syariah Hotel Solo. To face these conditions, the necessary strategy in the development related to hotel occupancy at Syariah Hotel Solo. The researcher is compelled to research more about the business strategy in the field of hospitality that is done by Syariah Hotel Surakarta in the middle of the pandemic Covid-19. This research uses qualitative method with descriptive approach. Carried out in Syariah Hotel Surakarta in the period of September 2020 until June 2021. Data collection using observation techniques, interviews and documentation. Data analysis using the method of data reduction, data presentation and drawing conclusions and verification to be able to provide the results of an overview of this research. The process of this research through the stages of monitoring the research object, take the formulation of the problem, analyze with the approach of the theory in providing an explanation of the phenomenon of study and the latter is to draw conclusions in general.Syariah Hotel Surakarta has now become one of the hotels based on sharia, which has been applying the new normal tourism at the time of the pandemic Covid-19. Syariah Hotel Surakarta have made every effort in developing business strategies with more direct to the aspects of the creative and innovative aspect by forming new configuration. Strategy in the marketing which is done by the Syariah Hotel Surakarta in the pandemic Covid-19 is the marketing through the medium of the newspaper, the internet, local television channels, radio and social media. The main strategy Syariah Hotel Surakarta with the implementation schedule Staycation. A Staycation is a travel deals by doing activities that are carried out in Syariah Hotel Solo. Activities this emphasizes the utilization of all facilities and infrastructure that exist in Syariah Hotel Solo. So guests can keep doing both at once carry out the policy of the government not to do a lot of outdoor activity.